2017
DOI: 10.17576/ajag-2017-08-11
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value Added and Traditional Accounting Measures for Shareholder’s Wealth Creation

Abstract: This paper investigated performance measurement tools and shareholder's wealth relationships in the context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…In the first step, to tackle homogeneity issues, the study used the unit root test as suggested by [61] for a cointegration modeling process. Once it was confirmed that there was no homogeneity issue and the variables were in the order of interest, a test of the cointegration was examined to know whether the variables were co-integrated or not [58].…”
Section: Statistical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step, to tackle homogeneity issues, the study used the unit root test as suggested by [61] for a cointegration modeling process. Once it was confirmed that there was no homogeneity issue and the variables were in the order of interest, a test of the cointegration was examined to know whether the variables were co-integrated or not [58].…”
Section: Statistical Resultsmentioning
confidence: 99%
“…The long-term beta coefficient for CO 2 emissions and economic growth were π 1 and π 2 respectively. Since the study was based on panel data, as such, the long-run panel cointegration specifications applied in previous studies [57,58] were employed. The error term ε t was assumed to be identically distributed.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Table 3 presents the basic characteristics of the variables in the study showing the mean, median, maximum, minimum, standard deviation, skewness, kurtosis, Jarque-bera and probability statistics. The Jarque-bera supported the normal pattern of the variable and represented the peak by kurtosis [35,36]. The mean value of bitcoin was found to be $12302.46 which is quite lower as compared to the current price of $16700 as of 20 December 2022.…”
Section: Resultsmentioning
confidence: 60%
“…The beta coefficients , , and represent fertiliser consumption, renewable energy consumption and agriculture’s share of GDP, respectively. The data set was in panel form, so the long-run cointegration specifications stated by Perron ( 1989 ) and Panigrahi ( 2017 ) were employed. The error term is assumed to be identically distributed.…”
Section: Methodsmentioning
confidence: 99%